Ultrafast solution treatment to improve the comprehensive mechanical properties of superalloy by pulsed electric current. (1st July 2021) - Qin, Shuyang; Hao, Jianqiao; Yan, Longge; Zhang, Xinfang
Abstract: The traditional solution (1120 °C/4 h) and aging (845-1080 °C/24 h) processes are the keys for K417G superalloy to obtain the expected microstructure and ensure excellent mechanical properties. It is found here that the investigated microstructure can be achieved by electropulsing solution treatment at 1000 °C, and the processing time is 10 minutes. Meanwhile, the morphology of the harmful γ/γ′ eutectic phase can be quickly modified during the pulsed process, thereby the crack propagation near the eutectic phase changes from a direct pass to a zigzag pass, which is beneficial to performance improvement. The theoretical analysis and calculation results show that high current density area existed between the heterogeneous phases and the system thermodynamic barrier reduction are the fundamental reasons for the primary γ′ dissolution and the γ/γ′ eutectic morphology evolution. Graphical abstract: Image, graphical abstract